Autoconocimiento emocional como principio fundamental para el rendimiento académico de los estudiantes del nivel educación básica - Peralta Naranjo, Merling Michelle (2025)
This study investigated emotional self-awareness as a fundamental principle for academic achievement in elementary school students, using a qualitative methodology that integrated theoretical review, theorization of selective codes, triangulation with specialists, and qualitative analysis of interviewees' experiences. The study addressed the links between emotional intelligence, critical pedagogy, the sociology of emotions, and cognitive theory, demonstrating that emotional self-awareness fosters identity, self-esteem, and self- regulation, in addition to reducing disruptive behaviors and strengthening classroom coexistence. The results showed a direct influence of emotional management on key cognitive processes such as attention and working memory, facilitating the establishment of study habits and the development of autonomy. This interpretation underpins the importance of integrating emotional approaches into pedagogical practices to enhance effective learning and comprehensive student well-being. The study concluded that emotional self-awareness operates as an organizer of learning and school life, highlighting the importance of teacher training and school-family partnerships to achieve sustainable changes and improvements in academic achievement.